An Indonesian Teacher’s Perceptions of Teacher-Students Relationship in EFL Classroom - Nathania, Aisa Ayudia; Sadiq, Nizamuddin (Unisia, 2024)
Empirical studies on teacher-student relationships (TSR) in both EFL and non-EFL contexts have been extensively explored. However, limited attention has been given to the role of human behavioral dimensions within classroom TSR practices. This study examines the specific human behavioral dimensions an Indonesian EFL teacher utilizes to foster TSR in her classroom. Data were gathered through semi-structured interviews using a qualitative research approach. The findings reveal that agency-related behaviors are less aligned with the teacher's interactions with students, whereas communion-related behaviors are more reflective of her classroom practices. These results suggest that Indonesian EFL teachers cultivate community in the classroom, emphasizing strong, positive relationships with their students.